Pengaruh Penggabungan Organisasi Perangkat Daerah Terhadap Kinerja Pegawai Di Dinas Sumber Daya Air, Cipta Karya Dan Tata Ruang Provinsi Sumatera Utara - Yunisari Theresia Zalukhu; Februati Trimurni (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
This study uses a quantitative method with SPSS version 29.0.0.0 software, namely the analysis using the Simple Linear Regression method which is used to determine the relationship between the regional apparatus organization variable (X) and the employee performance variable (Y). The data collection technique used is the distribution of questionnaires (questionnaire). The data source is primary data, respondents' answers are scored using a Likert scale. The total population of 193 employees and the number of samples in this study were 66 respondents.The results of the study indicate that there is a positive influence between the incorporation of regional apparatus organizations and the performance of employees at the Department of Water Resources, Human Settlements and Spatial Planning of North Sumatra Province. This is evidenced by the results of the variable reliability test, the reliability value is 0.961, so the reliability is good. According to Wiratna Sujerweni (2014), the questionnaire is said to be reliable if the Cronbach alpha value > 0.6 means that the items are very reliable as a data collection tool in this study.